2021
DOI: 10.3390/coatings11121555
|View full text |Cite
|
Sign up to set email alerts
|

High-Sensitivity Biosensor Based on Glass Resonance PhC Cavities for Detection of Blood Component and Glucose Concentration in Human Urine

Abstract: In this work, a novel structure of an all-optical biosensor based on glass resonance cavities with high detection accuracy and sensitivity in two-dimensional photon crystal is designed and simulated. The free spectral range in which the structure performs well is about FSR = 630 nm. This sensor measures the concentration of glucose in human urine. Analyses to determine the glucose concentration in urine for a normal range (0~15 mg/dL) and urine despite glucose concentrations of 0.625, 1.25, 2.5, 5 and 10 g/dL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…In addition, melatonin has a positive impact on the oxidative stress parameters, leading to a notable increase in serum SOD activity and total serum antioxidant capacity and may control the atherogenic index to influence cholesterol metabolism and control antioxidant activity with GSH and SOD [21][22][23][24][25][26][27][28][29][30]. Antioxidants are any chemical (molecule, compound, or enzyme) that has a substantial antioxidant effect.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, melatonin has a positive impact on the oxidative stress parameters, leading to a notable increase in serum SOD activity and total serum antioxidant capacity and may control the atherogenic index to influence cholesterol metabolism and control antioxidant activity with GSH and SOD [21][22][23][24][25][26][27][28][29][30]. Antioxidants are any chemical (molecule, compound, or enzyme) that has a substantial antioxidant effect.…”
Section: Resultsmentioning
confidence: 99%
“…The genetic diversity of H. pylori strains could explain the discrepancies in data about the relationship between H. pylori and diabetes. Significant geographic genetic diversity in particular virulence genes (cytotoxin-associated gene product (CagA), the vacuolating toxin (VacA), and the adhesion protein (BabA2) has been discovered, which contributes to the varying risk of H. Pylori infection's mixed clinical results [25,[29][30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…The cancer cells have classification and subclassifications based on large cell keratinizing, large cell non-keratinizing, and small cell nonkeratinizing categories regarded as well, moderately and poorly differentiated cancers, respectively [25]. However, conflicting reports suggest a poor prognosis of keratinizing variants in comparison compared to non-keratinizing variants of squamous cells.…”
Section: Discussionmentioning
confidence: 99%
“…Hence it was concluded that population-based screening programs in many countries assist in screening patients and enable extended survival of women displaying metastatic stages of cancer [12]. [25].…”
Section: Discussionmentioning
confidence: 99%